The effect of telerehabilitation on balance in stroke patients: is it more effective than the traditional rehabilitation model? A meta-analysis of randomized controlled trials published during the COVID-19 pandemic - Su, Zhaoyin; Guo, Zhenxia; Wang, Weitao; Liu, Yao; Liu, Yatao; Chen, Wanqiang; Zheng, Maohua; Michael, Nerich; Lu, Shuai; Wang, Weining; Xiao, Handan (Frontiers in Neurology, 2023)
Objective Telerehabilitation and telemedicine have gradually gained popularity. In 2019, the outbreak of COVID-19 started in Wuhan and then spread across the world. To date, most countries have opted to coexist with the virus. However, patients, especially those who have suffered a stroke, should take measures to avoid being infected with any disease as much as possible since any infectious disease can lead to adverse events for them. Telerehabilitation can be beneficial to stroke patients as they are less likely to be infected by the virus. In recent years, several studies on telerehabilitation have been conducted globally. This meta-analysis aimed to investigate the effects of telerehabilitation on the balance ability of stroke patients, compare the efficacy of conventional rehabilitation with telerehabilitation, explore the characteristics of telerehabilitation and conventional rehabilitation, and provide recommendations for rehabilitation programs in the context of the global pandemic. Methods We searched Pubmed, Embase, the Web of Science, and The Cochrane Library databases from 1 January 2020 to 31 December 2022 for randomized controlled trials published in English that evaluated the improvement of balance function in stroke patients after telerehabilitation and compared the differences between telerehabilitation (TR) and conventional rehabilitation (CR). The random-effects model was utilized to calculate mean differences (MDs) with 95% confidence intervals (CIs) to estimate intervention effects. Statistical heterogeneity was assessed according to the I2 values. The risk of bias was measured using the Cochrane risk-of-bias assessment tool. Results We included nine studies in the system evaluation, all of which were included in the pooled analysis. All outcomes in the experimental and control groups improved over time. The comparison between groups concluded that people who received the telerehabilitation intervention had a significant improvement in the Berg Balance Scale (MD = 2.80; 95% CI 0.61, 4.98, P < 0.05, I2 = 51.90%) and the Fugl-Meyer Assessment (MD = 8.12; 95% CI 6.35, 9.88, P < 0.05, I2 = 0) compared to controls. The Timed Up and Go test (MD = −4.59; 95% CI −5.93, –.25, P < 0.05, I2 = 0) and Tinetti Performance-Oriented Mobility Assessment—Balance (MD = 2.50; 95% CI 0.39, 4.61, P < 0.05) scored better in the control group than in the experimental group. There were no significant differences in other outcomes between the two groups. Conclusion Studies on changes in medical conditions during the COVID-19 pandemic also demonstrated that, for stroke patients, telerehabilitation achieves similar effects as the conventional rehabilitation model and can act as a continuation of the conventional rehabilitation model. Owing to the different equipment and intervention programs of telerehabilitation, its curative effect on the static balance and reactive balance of stroke patients may be different. Currently, telerehabilitation may be more conducive to the rehabilitation of patients' static balance abilities, while conventional rehabilitation is more effective for the rehabilitation of patients' reactive balance. Therefore, further studies are needed for investigating the difference in efficacy between varied devices and telerehabilitation programs. Further research is needed on static and reactive balance. In addition, such research should have a large body of literature and a large sample size to support more definitive findings based on the context of the COVID-19 pandemic. Systematic review registration CRD42023389456.